(untitled) (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2025)
This study argues that Cicero’s correspondence offers a privileged lens on the constitutional transgressions that reshaped the Roman Republic between 91 and 79 BCE. In Ad Atticum and Ad Quintum fratrem, the political, legal, and emotional aftershocks of the Social and Sullan wars are refracted through fear, exempla, and recollection, showing how trauma recalibrated what elites deemed constitutionally thinkable. The mos maiorum emerges not as a fixed code but as a living customary matrix – often negotiating with, and at times resisting, lex – that could be stretched under pressure. Tracing how extraordinary measures – marching on Rome, proscriptions, and the manipulation of magistracies – crossed the threshold into ordinary politics, the article reconstructs the mechanisms by which crisis was normalised and legality became the idiom of domination. Acknowledging Cicero’s conservative bias and retrospective stance, it contends that the letters remain indispensable for understanding elite concepts of legitimacy, legality, and political change: a passage from crisis response to constitutional habit culminating in a novus mos. Within a broader legalisation of fear, measures such as the lex Iulia and lex Plautia Papiria redefined inclusion as control, turning legality into a performative mask of coercion.